46 THE IMPACT OF THE INTRODUCTION OF STRUCTURED DOCUMENTATION ON A MULTI-DISCIPLINARY TEAM MEETING AS MEASURED BY CLINICAL AUDIT. (25th October 2022) - Fitzgerald, M
Abstract: Background: The typical method for multidisciplinary teams (MDT) to coordinate care in a rehabilitation setting is by holding weekly meetings. These MDT meetings are not always effective, with poor communication and vague plans of treatment leading to a lack of progress with rehabilitation and even delayed patient discharge. Methods: The MDT of the older person's rehabilitation unit aimed to improve their MDT meeting. A series of meetings, open to all members, identified the key issues. These were; variation in the level of contribution from attending disciplines, a lack of clarity on patients' current status, a lack of SMART goals being set and Predicted Dates of Discharge (PDD) not being set. This was confirmed by clinical audit examining contribution levels of attending disciplines across four questions. The proposed solution was a structured document called the Collaborative Rehabilitation Plan (CRP) booklet for use at MDT meetings, which was designed by a subcommittee with feedback from the full group. The audit was repeated after a one-month trial of the booklet. Results: The average contribution was highest on the current status of the patient (59%), and this was not changed post-booklet (59%). This was lower regarding the setting of goals (18%), and this improved post booklet (40%). The average contribution was lowest for the goals meeting SMART criteria (4%). This improved post booklet (28%). Improvement was also seen in the setting of PDDs (from 27% to 52%). While the level of contributions from all disciplines improved after the introduction of the booklet (from 27% to 42%) there was still a wide degree of variation. Conclusion: The development of the CRP booklet was of value in increasing the contributions of the team in a number of key areas. Contributions were still low in some areas and further work is needed to improve this.